TEACHING SCHOOL CHILDREN THROUGH SONGS ANG PICTURES - Eshniyozova Jasmina Jo’rabekovna; Eshonqulova Sarvinoz Yashinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation:This article discusses the growing trend of incorporating songs and pictures into educational practices as a way to make learning more engaging and effective for students. The paper emphasizes the significant role of rhythm and repetition in songs, which aids in memory retention and understanding. It explores how these methods benefit various subjects such as language acquisition, math, and science by appealing to different learning styles—auditory and visual. Songs not only help with vocabulary acquisition and pronunciation but also assist in teaching numbers, sequences, and other factual information, making learning more enjoyable and less monotonous. Additionally, the paper highlights the emotional impact of music, suggesting that songs can strengthen the connection between students and the material being taught. Ultimately, the integration of songs and pictures supports a more dynamic learning environment that fosters both engagement and retention.